Trichoglottis corazoniae (Orchidaceae: Vandeae: Aeridinae), a new species from the Philippines - Naive, Mark Arcebal K.; Martyr, John Clifton (Lankesteriana: International Journal on Orchidology, 2018)
A new species of Trichoglottis (Orchidaceae; Epidendroideae; Vandeae), Trichoglottis corazoniae Naive & Martyr, apparently endemic to Negros island, is here described and illustrated. It is closely similar to T. tamesisii but distinct by having forward-pointing stelidia with the upper surface being pubescent, larger flowers and a longer inflorescence. Information on the distribution, ecology and phenology are provided.